Gender Differences in the Difficulty in Disengaging from Threat among Children and Adolescents With Social Anxiety - Zhang, Peng; Ni, Wenjin; Xie, Ruibo; Xu, Jiahua; Liu, Xiangping (Frontiers in Psychology, 2017)
There is some research showing that social anxiety is related with attentional bias to threat. However, others fail to find this relationship and propose that gender differences may play a role. The aim of this study was to investigate the gender differences in the subcomponents of attentional bias to threat (hypervigilance and difficulty in disengaging) among adolescents with social anxiety. Overall, 181 children and adolescents aged between 10 and 14 participated in the current study. Images of disgusted faces were used as threat stimuli and an Exogenous Cueing Task was used to measure the subcomponents of attentional bias. Additionally, the Social Anxiety Scale for Children was used to measure social anxiety. The repeated measurement ANOVA showed that male participants with high social anxiety showed difficulty in disengaging from threat, but this was not the case for female participants. Our results indicated that social anxiety is more related with attentional bias to threat among male adolescents than females. These findings suggested that developing gender-specific treatments for social anxiety may improve treatment effects.